STRATEGI PENGEMBANGAN KETAHANAN PANGAN RUMAH TANGGA PETANI PADA DAERAH RAWAN BANJIR DI KABUPATEN BOJONEGORO - Supardi, Suprapti; Riptanti, Erlyna Wida; Qonita, Aulia (Jurnal AGRISEP, 2014)
This research aim to make the development strategy of food security in farmer household at flood prone area in Bojonegoro. The location decided by purposive random sampling. The methode that used SWOT analysis. The research shows that the food security on the fourth quadrant. The development strategy at this quadrant is stability. This strategy consist of a) Introduction technology of floating rice in flood area. b) Improvement program P2KP. c) Improvement Demapan. d) Living harmony with flood, e) Introduction rice seeds that stand with poll water. f) Establish the barn at village, g) Establishment the barn at farmer household, h) Early warning system, i) Control the pets and diseses of plant, j) Development of horticultural crops on former flooding land. k) Making strategic planning of food security in Food Security Office.